Detective story [videorecording (DVD)] - Wyler, William, 1902-1981; Douglas, Kirk, 1916-2020; Parker, Eleanor, 1922-2013; Bendix, William, 1906-1964; Kingsley, Sidney, 1906-1995 (Paramount, 2018)
An embittered cop neglects his wife as he leads a New York precinct of characters in their grim battle with the city's lowlife.